Evaluation of Heavy Metals Contamination from Environment to Food Matrix by TXRF: The Case of Rice and Rice Husk - Fabjola Bilo (Journal of Chemistry, 2015)
This paper is devoted to the chemical analysis of contaminated soils of India and the rice grown in the same area. Total reflection X-ray fluorescence spectroscopy is a well-established technique for elemental chemical analysis of environmental samples, and it can be a useful tool to assess food safety. Metals uptake in rice crop grown in soils from different areas was studied. In this work soil, rice husk and rice samples were analyzed after complete solubilization of samples by microwave acid digestion. Heavy metals concentration detected in rice samples decreases in the following order: Mn > Zn > Cu > Ni > Pb > Cr. The metal content in rice husk was higher than in rice. This study suggests, for the first time, a possible role of heavy metals filter played by rice husk. The knowledge of metals sequestration capability of rice husk may promote some new management practices for rice cultivation to preserve it from pollution.